FUNCTIONAL PARTS OF SPEECH (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the major functional parts of speech in English, focusing on their structural, semantic, and discourse-organizing roles within the grammatical system. Unlike content words, which carry lexical meaning, functional categories provide relational and grammatical information that shapes syntactic structure and textual cohesion. The study outlines the nature of articles, prepositions, conjunctions, auxiliary and modal verbs, pronouns, determiners, particles, and interjections, emphasizing their distinct behaviors and contributions to linguistic organization. Historical perspectives—from traditional grammar to structuralist, generative, and corpus-based approaches—are incorporated to highlight shifts in classification and methodology. The analysis also addresses cross-linguistic challenges, especially for speakers of article-less or case-based languages such as Uzbek, demonstrating the pedagogical and translational implications of functional categories. Ultimately, the study underscores the centrality of function words in encoding grammatical relationships, guiding interpretation, and enabling effective communication.